Beyond milk : framing milk and oat-drink campaigns in Sweden - Rigo Cavinato, Maria Eduarda (SLU/Dept. of Urban and Rural Development, 2018)
The growing demand for products that cause minimal environment impact and follow a sustainable production system allow new brands and marketing concepts to compete with traditional companies and well established products on the market. Through Facebook and Instagram, companies are able to connect with their consumers and present their own point of view on many different subjects. By analyzing 50 online publications from two Swedish companies, Oatly producing oat-drink and Arla producing milk, it was possible to identify the different frames used in their social-media campaigns when referring to environmental issues caused by especially, the milk production system. Besides, which frames they use when communicating social and cultural values in relation to milk production and consumption in Sweden. Through a content analysis and by applying the framing theory, it was possible to outline and interpret the standpoint Oatly and Arla shared with their online viewers and potential customers on their social media campaigns. The findings suggest that, milk in Sweden is culturally accepted and play an important role in the Swedish diet, especially considering its health benefits. While oat-drink challenge the conventional frames presented by the milk industry, being set as a sustainable option and an alternative to animal milk, focusing its marketing towards a newer generation that is interested in creating new habits and changing social patterns.